Early vs. Delayed Initiation of Treatment With P2Y12 Inhibitors in Patients With Non-ST-Segment Elevation Acute Coronary Syndrome: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Vicent, Lourdes; Diaz-Arocutipa, Carlos; Tarantini, Giuseppe; Mojoli, Marco; Hernandez, Adrian V.; Bueno, Héctor (Frontiers in Cardiovascular Medicine, 2022)
Aims: Whether early or delayed dual antiplatelet therapy initiation is better in patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) is unclear. We assessed the evidence for comparing the efficacy and safety of early versus delayed P2Y12 inhibitor initiation in NSTE-ACS. Methods: Randomized controlled trials with available comparisons between early and delayed initiation of P2Y12 inhibitors (clopidogrel, prasugrel, ticagrelor) in patients with NSTE-ACS until January, 2021 were reviewed. Primary outcomes were trial-defined major adverse cardiovascular events (MACE) and bleeding. Secondary outcomes were all-cause mortality, cardiovascular mortality, myocardial infarction, stent thrombosis, urgent coronary revascularization, and stroke. Frequentist random-effects network meta-analyses were conducted, ranking best treatments per outcome with p-scores. Results: Nine trials with intervention arms including early and delayed initiation of clopidogrel (n=5), prasugrel (n=8) or ticagrelor (n=6) involving 40,096 patients were included. Early prasugrel (hazard ratio [HR], 0.59; 95% confidence interval [95%CI], 0.40-0.87), delayed prasugrel (HR, 0.60; 95%CI 0.43-0.84), and early ticagrelor (HR, 0.84; 95%CI, 0.74-0.96) significantly reduced MACE compared with early clopidogrel, but increased bleeding risk. Delayed prasugrel ranked as the best treatment to reduce MACE (p-score=0.80), early prasugrel to reduce all-cause mortality, cardiovascular mortality, stent thrombosis, and stroke, and delayed clopidogrel to reduce bleeding (p-score=0.84). The risk of bias was low for all trials. Conclusion: In NSTE-ACS patients, delayed prasugrel initiation was the most effective strategy to reduce MACE. Although early prasugrel was the best option to reduce most secondary cardiovascular outcomes, it was associated with the highest bleeding risk. The opposite was found for delayed clopidogrel.